Penggunaan E-Modul Untuk Meningkatkan Konsep Literasi Keuangan Siswa Primary VI SD Focus Independent School Surakarta - Frederika Widi Prihartanti; Wiedy Murtini; Mintasih Indriayu (LPPM Universitas Putera Batam, 2022)
A Covid- 19 pandemic that cause economic disruption in different ways requires financial skills. The skill can be obtained through education in schools. Financial literacy education is a crucial thing to be inserted in the learning program at school. Based on observations, the implementation of financial literacy learning at SD Focus Independent School Surakarta is still not well structured. The concept of finance is indirectly taught in thematic learning. The pandemic has made students more intensive in using digital technology. The use of E-modules is an alternative in systematically delivering financial concepts. The method in this research is Classroom Action Research (CAR) with four stages: planning, action, observation and reflection. The study was undertaken by all Primary 6 Focus Independent School students in 2021/2022 academic year. The total number of students who participated in the study were 40 students, consisting of 22 female students and 18 male students. The instruments (data collection tools) used are questions and observation sheets. Based on the results of the study, it was revealed that there was an increase in student evaluation results related to understanding the concept of financial literacy. In the first cycle, students have an average of 69.75 while in the second cycle has an average of 80.75. Therefore, the use of E-modules can improve the concept of financial literacy for Primary VI students at Focus Independent School Surakarta in 2021/2022.